Parental Nurturing Values and Child Religious Formation through the Peurateb Aneuk Tradition in Lhokseumawe, Aceh - Farhan, Muhammad; Pahlevi, Mohd Reza; Nurhayati, N (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Parenting is a series of obligations that must be carried out by parents. If parenting is not done properly and appropriately, various problems and conflicts will often arise, both within the child and between the child and parents, as well as with the surrounding environment. The condition of society in general is very unfortunate. It has undergone changes, and the implementation and use of traditions based on local wisdom have been increasingly displaced in everyday life. Traditional values are even being almost eliminated and forgotten. The essence of traditions is now beginning to be forgotten with the influx of foreign cultures. Millennial mothers today generally tend to prefer to raise their children in a modern environment that is far from religious values. This can have an impact on the formation of children's characters that are not in line with expectations, deviating from the norms established in Islamic teachings, and making them less able to deal with various life problems. The purpose of this study is to determine the values of parenting in shaping children's religiosity through the peurateb aneuk tradition in the city of Lhokseumawe. This study employs a descriptive qualitative method with a phenomenological approach. Data collection was conducted through observation, interviews, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are values of faith parenting, including the pillars of faith; values of moral parenting, including obedience and respect; and values of worship parenting, including the pillars of Islam.